Penyuluhan Pendidikan Islam: Upaya Penyadaran dan Pencegahan Tindak Kekerasan Seksual Berbasis Al-Qur'an - Achmad Junaedi Sitika; Muhamad Taufik BK; Ahmad Syahid (Al-Qalam Institute, 2022)
This community service aims to provide students withinsight and awareness of sexual violence and how to preventit. The method used is counseling and question and answer.The results show that students' insight increases byparticipating in counseling activities. Those who wereinitially unfamiliar with sexual violence gainedenlightenment about what sexual violence is, its forms,criminal law sanctions, and ways to prevent them. Funlearning and question-and-answer activities by placingoneself as a facilitator have proven to be effective instimulating students' critical thinking skills, active learning,and communication skills. The recommendations are theneed for training that leads to entrepreneurial skills witheconomic value and profits that are useful for students'progress and Islamic boarding schools